Does housing allowance feed through into rental prices? - Matti Virén (Bank of Finland, 2011)
This paper deals with the incidence of housing subsidies, which is analysed using Finnish panel data. The main data set comprises 50 000 households that received housing allowances during the period 2000 2008. In addition, we utilize repeated cross-sections of all Finnish households for 1989 2008, the annual sample exceeding 10 000. Estimation results suggest that a part of the subsidies will indeed feed through into rental prices. A conservative estimate of the size of the feed-through is one-third, but it is certainly possible that the number is, in reality, as high as 50 per cent. On the other hand, the subsidy seems to have increased housing demand more than the subsidy-induced income effect would have implied, which is in accordance with the goals of the subsidy programme. Our results seem to be consistent with other studies, which have also indicated relatively high rent effects. If this is indeed the case, we are advised to reconsider the need for reforming the system of housing subsidies, at least with regard to the share of costs that remains on households own accounts and the implicit indexation of the system.
URN:NBN:fi:bof-20140807233
Keywords: 330